The creative class, bohemians and local labor market performance: a micro-data panel study for Germany 1975-2004 - Joachim Möller; Annie Tubadji (Osteuropa-Institut Regensburg, 2008)
The paper aims at testing Florida's concept of the Creative Class using panel data for 323 West German regions for the time period 1975-2004. We apply two different es-timation methods, a panel VAR for the complete data set and a dynamic system ap-proach based on GMM for a modified data set collapsed to six five-year periods. We find that the local concentration of the Creative Class has predictive power for the economic development of a region and tends to outperform traditional indicators of human capital. However, our results do not support Florida's assertion that the creative workers flock where the Bohemians are. According to our findings, the Creative Class is attracted by favorable economic conditions as indicated by employment growth or an increasing wage bill.
Keywords: Z10; C23; R1; O1; O3; 330; Culture; Regional Development; Bohemians; Creative Class; Dynamic Panel Methods; Kreativsektor; Regionale Entwicklung; Schätzung; Alte Bundesländer